Situated learning for adults acquiring a second language - Rigoberto Castillo; Juan Carlos Vargas (Universidad de La Sabana, 2013)
This article reports a case study of a group of English Language Learners involved in an outreach course which forms part of the social project Bogota Humana. To give meaning to learning another language (L2) the project held sessions inside and outside the classroom. The inquiry was directed on the perceptions of the local context and on its usefulness in L2 acquisition. It was found that outdoor spaces offer participants a sense of comfort which encourages participation and social interaction. They felt their identity, as adults and as citizens of the capital, was acknowledged.